1998
DOI: 10.2466/pr0.1998.82.3.1051
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of Basic Concepts by Children with Intellectual Disabilities Using a Computer-Assisted Learning Approach

Abstract: Computer-assisted learning can be an efficient learning-teaching procedure. Although there is an extensive educational software tradition for this approach, few have better performance than standard drill-and-practice methods. In this work, the specific software "Let's Play With..." was designed to teach concepts of colours, shapes, and body position to children with intellectual disabilities. The software structure follows the Gagné instructional design and applied behaviour analysis. The program was carried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
4
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…Moreover, that students with disabilities in this study differentially benefited from the use of technology to deliver the content in the WFA price is consistent with emerging research pertaining to universal design for learning and the use of technology to promote outcomes for students with cognitive disabilities (Wehmeyer, Smith, & Davies, 2006). It also supports the more general finings that computer-assisted learning provides clear advantages to students with disabilities (Alcalde, Navarro, Marchena, & Ruiz, 1998;BernardOpitz, Sriram, & Nakhoda-Sapuan, 2001;Blischak & Schlosser, 2003;Davies et al, 2003;Elder-Hinshaw & Manset-Williamson, 2006;Raskind & Higggins, 1995;.…”
Section: Summary Of Findingssupporting
confidence: 60%
“…Moreover, that students with disabilities in this study differentially benefited from the use of technology to deliver the content in the WFA price is consistent with emerging research pertaining to universal design for learning and the use of technology to promote outcomes for students with cognitive disabilities (Wehmeyer, Smith, & Davies, 2006). It also supports the more general finings that computer-assisted learning provides clear advantages to students with disabilities (Alcalde, Navarro, Marchena, & Ruiz, 1998;BernardOpitz, Sriram, & Nakhoda-Sapuan, 2001;Blischak & Schlosser, 2003;Davies et al, 2003;Elder-Hinshaw & Manset-Williamson, 2006;Raskind & Higggins, 1995;.…”
Section: Summary Of Findingssupporting
confidence: 60%
“…This period was also characterized by the emergence of studies connected to augmented communication [ 62 ] and to the use of robotics [ 63 ]. In this regard, Alcade et al [ 64 ] observed that computer-assisted learning can be an efficient learning–teaching procedure for children with neurodevelopmental disorders. A specific software called “Let’s Play With…” was designed to teach the concepts of colors, shapes, and body positions.…”
Section: Ict As a Support For The Aba Modelmentioning
confidence: 99%
“…The children with autism spent more time on reading material when they accessed it through a computer and were less resistant to the use of this technology in learning. Alcade et al [3] evaluated the effectiveness of the software ''Let's play with...'', an interactive multimedia program that teaches shapes, colours and concepts of body position to children with intellectual disabilities. The study was based on the principles of Gagne instructional design and applied behaviour analysis [3].…”
mentioning
confidence: 99%
“…Alcade et al [3] evaluated the effectiveness of the software ''Let's play with...'', an interactive multimedia program that teaches shapes, colours and concepts of body position to children with intellectual disabilities. The study was based on the principles of Gagne instructional design and applied behaviour analysis [3]. One of the strengths of this study is that it examines the learning methods of children with intellectual disabilities.…”
mentioning
confidence: 99%
See 1 more Smart Citation